Keefektifan Penerapan Model Pembelajaran Direct Instruction dalam Pembelajaran Biologi Materi Kingdom Monera pada Siswa Kelas X MAN 1 Makassar - Taufiqah, Afra; Hamka L, Hamka L; Karim, Hilda (Biology Teaching and Learning, 2019)
Abstract. This study is a quasi experimental research design with one group pretest-posttest design that aims to determine the effectiveness of the application of direct instruction learning models in the study of biology in kingdom monera material. The study sample was randomly selected and selected class X MIA 2 as the experimental class. Data collection techniques through giving tests before (pretest) and after (posttest) learning to measure student learning outcomes and observation of learning activities of students during the learning process. The data analysis technique used is descriptive and inferential statistical analysis with t test. The results showed that the direct instruction learning model was effectively applied in the biology learning class X MAN 1 Makassar in Kingdom Monera material. Improved student learning outcomes are seen in the normalized gain average of 0.7423 which is in the high category. The proportion of students who reach KKM or in the complete category after being taught with Direct Instruction learning model is 78.95%. The activities of students as much as 81.58% are in the active category. Keywords: direct instruction, learning outcomes, learning activities.